2007
DOI: 10.1093/europace/eum208
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillatory cycle length: computer simulation and potential clinical importance

Abstract: Atrial fibrillatory cycle length is inversely associated with the number of sources participating in AF maintenance observed in the computer model. In addition, AFCL is an important predictor of baseline duration of the arrhythmia, type of AF, and ease of catheter ablation therapy to terminate AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 20 publications
8
83
1
1
Order By: Relevance
“…In one analysis presented by Haïssa-guerre et al, 11 patients with structural heart disease admitted for catheter ablation of AF had significantly lower AFR than those with structurally normal hearts, supporting our observation in MUSIC material. Because no information on the AF duration at inclusion in MUSIC study was collected, we have not been able to analyze whether observed AFR values correlate with the duration of the arrhythmia, which is a limitation of our study.…”
Section: Afr In Af Intervention Studies and Findings In Music Af Cohortsupporting
confidence: 88%
See 2 more Smart Citations
“…In one analysis presented by Haïssa-guerre et al, 11 patients with structural heart disease admitted for catheter ablation of AF had significantly lower AFR than those with structurally normal hearts, supporting our observation in MUSIC material. Because no information on the AF duration at inclusion in MUSIC study was collected, we have not been able to analyze whether observed AFR values correlate with the duration of the arrhythmia, which is a limitation of our study.…”
Section: Afr In Af Intervention Studies and Findings In Music Af Cohortsupporting
confidence: 88%
“…Clinical observations confirmed these findings, 10 and the link between slower AFR and better outcome of interventions for persistent AF have been reported, both for cardioversion 4 and catheter ablation of AF. 7,11 However, refractoriness of atrial myocytes is not the only determinant of AFR. Ablation in the left atrium that creates boundaries hindering propagation of fibrillatory waves prolongs the AF cycle length measured in the right atrial appendage.…”
Section: Age-related Afr Slowingmentioning
confidence: 99%
See 1 more Smart Citation
“…19 AFCL is inversely proportional to the number of drivers maintaining AF, and hence AFCL prolongation is thought to reflect elimination of drivers. 20 AFCL has been used by others to monitor response to ablation, with an increase Ն5-6 ms considered significant. [21][22][23] Mean AFCL was determined manually over 30 cycles from bipolar electrograms recorded at the apex of the left and right atrial appendages, where electrograms are high-voltage and hence AFCL is unambiguous, before and after ablation of each CFAE lesion.…”
Section: Assessment Of Afclmentioning
confidence: 99%
“…If AF does not terminate or is re-inducible after termination, we assess for AF cycle length prolongation >10 %, that indicates elimination of a secondary AF source in our studies and in prior computer simulations (that used a more lenient 3-4 % cutpoint). 46,47 We then used a composite acute endpoint of 'hyperacute' AF termination (with non-re-inducibility) or ≥10 % slowing.…”
Section: Targeted Ablation Only At Rotors and Focal Sources Acutely Tmentioning
confidence: 99%